SmartPark / Darveena Debbie Blaise … [et al.] - Blaise, Darveena Debbie; Babang, Gloria Piper; Sidi, Heather Gesai; Nordin, Ivyliana; Gatu, Alvin (Faculty of Computer and Mathematical Sciences, 2022)
Parking facilities are vital components of the roadway system as every vehicle trip needs proper parking at its destination. Parking space will be the first component to be exposed to potential customers, providing them with the first-hand experience that people will face during their visit to the destinations. Certainly, users will be frustrated if they are faced with difficulties in finding parking spaces such as due to them being inadequate, inconvenient, or expensive. Conflict and confusion arise among several people due to common parking issues such as inadequate parking availability information, inefficient use of existing parking capacity and difficulties with parking ticket fee regulation. The SmartPark application is a feature-rich application with its main objective being to ensure the convenience of vehicle users in terms of parking. This all-in-one, environmentally friendly application offers services such as a contactless e-payment function for parking fees and displays directional ways of finding vacant parking spaces even from outside of the building. Apart from that, a feature highlighted as its novelty is the function of locating your vehicle with exact coordinates as pinned the moment one has parked. Functioning similarly to a map, one can head to their car without worrying about which floor, or which section they park at. Furthermore, with its e-wallet concept utilised for parking fee payment, there is also a reminder feature for when one must top up their balance if it is running low to avoid fuss during times when payment needs to be done.